2013
DOI: 10.1037/a0029927
|View full text |Cite
|
Sign up to set email alerts
|

Electronic diary assessment of the temporal association between proximal anger and intimate partner violence perpetration.

Abstract: Objective: The temporal association between proximal anger and intimate partner violence (IPV) perpetration was examined using electronic daily diary assessment methodology. In addition, relevant demographic and relational variables were examined as potential moderators of the association between anger and IPV perpetration. Method: Participants were 184 men and women in dating relationships who completed daily surveys reporting anger and IPV for a period of 2 months. Results: Increases in proximal anger were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 44 publications
8
40
0
Order By: Relevance
“…Participants were asked to indicate, using a BYes/No^format, whether they had engaged in any of the acts of aggression for each subscale the previous day. For both types of aggression separately, participants who reported perpetration were coded with a B1^and participants who reported no perpetration were coded with a B0.^This assessment and scoring method is consistent with other daily diary studies of IPV (e.g., Elkins et al 2013;Moore et al 2011;Stuart et al 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were asked to indicate, using a BYes/No^format, whether they had engaged in any of the acts of aggression for each subscale the previous day. For both types of aggression separately, participants who reported perpetration were coded with a B1^and participants who reported no perpetration were coded with a B0.^This assessment and scoring method is consistent with other daily diary studies of IPV (e.g., Elkins et al 2013;Moore et al 2011;Stuart et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…In a 60-day prospective daily diary study, Elkins, Moore, McNulty, Kivisto, and Handsel (2013) demonstrated that the odds of psychological (OR=2.78), physical (OR=2.38), and sexual aggression (OR=2.27) perpetration were increased when daily angry affect was high (a combination of anger, hostility, and irritability). This study utilized a college student sample and had participants rate their affect prior to seeing a dating partner each day.…”
mentioning
confidence: 98%
“…For instance, research on psychological and physical aggression has demonstrated a number of risk factors for perpetration, including trait and state anger (Elkins et al 2013;Parrott and Zeichner 2003), difficulties with emotion regulation (Shorey et al 2011a), mental health symptoms (e.g., PTSD symptoms; Taft et al 2010), witnessing violence in childhood (Carr and Vandeusen 2002), Cluster B personality traits (Hines 2007), and alcohol use (Shorey et al 2011d). It is plausible that these same factors are associated with the perpetration of stalking behaviors.…”
Section: Directions For Future Researchmentioning
confidence: 96%
“…In a daily diary study, higher proximal anger was also related to a greater probability of perpetrating IPA among a sample of undergraduate students (Elkins, Moore, McNulty, Kivisto, & Handsel, 2013). Together, these findings suggest that negative emotion, and anger specifically, may be proximal risk factors for IPA perpetration.…”
mentioning
confidence: 68%